1982
DOI: 10.1111/j.1471-4159.1982.tb10880.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Identification of Brain Proteins on Cellulose Nitrate in Human Demyelinating Disease

Abstract: An immunological technique has been employed to identify proteins, separated in polyacrylamide gels, which show changes in brain samples from cases of multiple sclerosis and subacute sclerosing panencephalitis. Sodium dodecylsulphate‐treated proteins in particulate and soluble fractions were separated in polyacrylamide slab gels, transferred electrophoretically onto cellulose nitrate sheets, incubated with specific antisera and visualized by an immunoperoxidase method. Protein bands showing changes were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…Our studies have shown that the NH2-terminus is heterogeneously acylated with alkyl carboxylates varying in length from [2][3][4][5][6][7][8][9][10] detected at this time. From the age of 4 yr, the adult proportion of C-8 was obtained i.e., -20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies have shown that the NH2-terminus is heterogeneously acylated with alkyl carboxylates varying in length from [2][3][4][5][6][7][8][9][10] detected at this time. From the age of 4 yr, the adult proportion of C-8 was obtained i.e., -20%.…”
Section: Discussionmentioning
confidence: 99%
“…Two (6). At least three variants have been reported in the human brain, the 21.5-, 18.5-, and 17.3-kD sizes (7)(8)(9)(10)(11). These variants are believed to arise by alternate splicing of a single message.…”
Section: Introductionmentioning
confidence: 99%
“…40) The immunohistological characteristics of multiple sclerosis, one of the most well-known demyelinating diseases, have frequently been described. 15,30) Degeneration of the corpus callosum was found in a patient with multiple sclerosis. 12) Furthermore, MR imaging of patients of Alzheimer's disease, which is typically characterized by dementia, showed white matter change in about 60% of the brain tissue.…”
Section: Comparison With Other Types Of Dementia Diseasementioning
confidence: 99%
“…Monoclonal antibodies A2B5 and anti-human fibronectin F9 (Sera-Lab), human macrophage marker antibody EBM/II (Franklin et al, 1986) (Dakopatts), and normal mouse and rabbit serum (Nordic) were also used. The myelinoligodendrocyte and GFAP antibodies have been characterized on immunoblots and human brain tissue sections, and we have examined the specificity of the glutamine synthetase and EBM/11 antibodies on sections (Newcombe et al, 1982(Newcombe et al, , 1988. Anti-mouse or anti-rabbit immunoglobulin G (IgG) or F(ab), fragments conjugated to fluorescein or rhodamine isothiocyanate (FITC) (Serotec, Dakopatts and Sigma) were used at a 1 : 20 dilution.…”
Section: M M U N O C Y T O C H E M I C a L S T A I N I N Gmentioning
confidence: 99%
“…The following mouse monoclonal antibodies were gifts: anti-neurofilament antibody RT97 (from Dr B. Anderton), anti-bovine myelin basic protein (MBP) (Groome, Harland & Dawkes, 1985) and anti-rat galactocerebroside (Ranscht et al, 1982). The following rabbit antisera were also gifts: anti-human Wolfgram protein from Dr E. Bock (Newcombe, Glynn & Cuzner, 1982), anti-human carbonic anhydrase isoenzyme I1 (CA 11) (Komoly et al, 1987) and anti-human glutamine synthetase from Dr N. Gregson, and anti-rat myelin associated glycoprotein (MAG) from Dr R. Quarles (Newcombe et al, 1982).…”
Section: M M U N O C Y T O C H E M I C a L S T A I N I N Gmentioning
confidence: 99%